Advanced Cellulosic Materials for Treatment and Detection of Industrial Contaminants in Wastewater. Issue 15 (16th September 2016) - Wayland, Hunter A.; Boury, Susan N.; Chhetri, Bijay P.; Brandt, Andrew; Proskurnin, Mikhail A.; Filichkina, Vera A.; Zharov, Vladimir P.; Biris, Alexandru S.; Ghosh, Anindya
Abstract: The scarcity of fresh, clean water is one of the most tremendous global crises currently facing the human race. Various technologies exist for the treatment of contaminated water on different waste volume scales, for specific pollutants, and at a range of cost points. The use of agricultural and industrial by‐products directly or with simple modifications for treating wastewater has been investigated thoroughly, and the new frontier in this field is the development of advanced cellulose materials which are low cost, highly efficient, and widely applicable. Concurrently, developing highly sensitive and selective methods for analyzing the remediation efficiency of these materials is important as low concentrations of industrial contaminants can cause severe health problems in humans. The focus of this review is current progress in advanced cellulose materials for treatment of industrially‐contaminated wastewater, particularly that which contains dyes, heavy metals, and petrochemicals, and the development of ultrasensitive technologies such as photothermal spectroscopy (PTS) and photoacoustic spectroscopy (PAS) for pollutant detection. Abstract : Cellulose may be sourced from trees, agricultural by products, and industrial waste products for producing materials for the removal and detection of industrial water contaminants such as dyes, heavy metals, and petrochemicals. These advanced materials have expanded the versatility and efficiency of natural resource based water treatment methods. Water treated with these materials may be reclaimed for use in other industrial sectors such as agriculture, and in fact, areas in Israel and the western United States have already begun using treated wastewater for crop irrigation.